The Cambridge companion to American science fiction (New York)
xxx, 254 s.
Keywords: "The Cambridge Companion to American Science Fiction explores the relationship between the ideas and themes of American science fiction and their roots in the American cultural experience. Science fiction in America has long served to reflect the country's hopes, desires, ambitions, and fears. The ideas and conventions associated with science fiction are pervasive throughout American film and television, comics and visual arts, games and gaming, and fandom, as well as across the culture writ large. Through essays that address not only the history of science fiction in America but also the influence and significance of American science fiction throughout media and fan culture, this companion serves as a key resource for scholars, teachers, students, and fans of science fiction." --